Teen Drinking and Educational Attainment: Evidence from Two‐Sample Instrumental Variables Estimates - Dee, Thomas S.; Evans, William N. (Journal of Labor Economics, 2003)
This study examines the effects of teen alcohol use and availability on educational attainment. We demonstrate that teens who faced a lower minimum legal drinking age (MLDA) were substantially more likely to drink. However, we find that changes in MLDA had small and statistically insignificant effects on educational attainment. Using matched cohorts from two data sets, we also report two‐sample instrumental variables estimates of the effect of teen drinking on educational attainment. These estimates are smaller than the corresponding ordinary least squares estimates and statistically insignificant, indicating that teen drinking does not have an independent effect on educational attainment.